Analysis of Learning Achievements of Identity Elements in Early Childhood Education Students in Jenawi District, Karanganyar Regency: Analisis Capaian Pembelajaran Elemen Jati Diri Pada Peserta Didik PAUD di Kecamatan Jenawi Kabupaten Karanganyar - Hidayah, Anisa Nur; Ali Formen; Diana (Pendidikan Guru PAUD Universitas PGRI Semarang, 2025)
Abstract Many pre-school children still experience psychosocial problems, especially social-emotional problems such as aggressive behavior or anxiety. which results in negative development and readiness to enter the next level of school. The purpose of the study was to determine the profile of the elements of learning outcomes of learners' identity in Jenawi District Kindergarten and to find out the teacher's approach in the elements of learning outcomes of learners' identity in the independent curriculum in Jenawi District Kindergarten. The research used is a type of quantitative descriptive research in this study aims to determine the learning outcomes of the elements of early childhood identity in Jenawi District. Respondents in quantitative research are children aged 4-6 years. The sample in this study is a total of 221 children who attend kindergarten institutions spread across Jenawi, Karanganyar. Data collection techniques using questionnaires, namely with favorable and unfavorable questions using a Likert scale. Descriptive percentage analysis is used. Data management is processed using Microsoft excel with the help of several formulas in Microsoft excel. The results of the final descriptive data analysis, the results of the calculation of the learning achievements of the elements of identity in PAUD students represented with a minimum value of 47 and a maximum value of 80. while the average is 65.51 with a standard deviation of 8.01. Abstrak Anak pra sekolah banyak yang masih mengalami masalah psikososial terutama masalah sosial emosional seperti perilaku agresif atau kecemasan. yang mengakibatkan negatif terhadap perkembangan dan kesiapan masuk sekolah jenjang selanjutnya. Tujuan penelitian yaitu untuk mengetahui Profil elemen capaian pembelajaran jati diri peserta didik di TK Kecamatan Jenawi dan Untuk mengetahui pendekatan guru dalam elemen capaian pembelajaran jati diri peserta didik dalam kurikulum merdeka di TK Kecamatan Jenawi. Penelitian yang digunakan adalah jenis penelitian deskriptif kuantitatif dalam penelitian ini bertujuan untuk mengetahui capaian pembelajaran unsur jati diri anak usia dini di Kecamatan Jenawi. Responden dalam penelitian kuantitatif adalah anak usia 4-6 tahun Sampel dalam penelitian ini yaitu sejumlah 221 anak yang bersekolah di lembaga Taman Kanak-kanak yang tersebar di Jenawi, Karanganyar. Teknik Pengumpulan Data menggunakan Kuesioner yaitu dengan pertanyaan favourable dan unfavourable menggunakan skala Likert. Analisis deskriptif persentase digunakan pengelolaan data diolah menggunakan Microsoft excel dengan bantuan beberapa rumus yang ada di Microsoft excel. Hasil analisis data deskriptif akhir, hasil perhitungan capaian pembelajaran elemen jati diri pada peserta didik PAUD yang diwakili dengan nilai minimum 47 dan nilai maksimum 80. sedangkan rata-rata adalah 65.51 dengan standar deviasi 8.01. Kata kunci: Elemen Identitas; Siswa Pendidikan Anak Usia Dini; Hasil Belajar